2022
DOI: 10.1097/pas.0000000000001870
|View full text |Cite
|
Sign up to set email alerts
|

HER2 Overexpression and Amplification in Uterine Carcinosarcomas With Serous Morphology

Abstract: Uterine carcinosarcoma (UCS) is an aggressive malignancy with few treatment options. A recent clinical trial has shown an increase in progression-free survival in patients with human epidermal growth factor receptor 2 (HER2)-positive serous endometrial carcinomas treated with anti-HER2-targeted therapies. Few studies have evaluated HER2 expression/amplification in UCS. Similar to serous endometrial carcinoma, the majority of UCS have TP53 mutations and a serous epithelial component, suggesting that UCS may sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Rottmann et al 52 recently showed that 16% of 80 gynecologic carcinosarcomas (including uterine carcinosarcoma) showed HER2 overexpression and amplification when using the 2013 ASCO/College of American Pathologists scoring system. Similar results were reported by several studies, 53,54 including by Yoshida et al 55 and Jenkins et al 56 The panel recommends HER2 IHC testing (with reflex to HER2 fluorescence in situ hybridization for equivocal IHC) for possible treatment of advanced-stage or recurrent serous endometrial carcinoma or carcinosarcoma. HER2 IHC testing should also be considered in TP53-mutated/p53 abnormal endometrial carcinoma regardless of histotype.…”
Section: Pathologysupporting
confidence: 78%
“…Rottmann et al 52 recently showed that 16% of 80 gynecologic carcinosarcomas (including uterine carcinosarcoma) showed HER2 overexpression and amplification when using the 2013 ASCO/College of American Pathologists scoring system. Similar results were reported by several studies, 53,54 including by Yoshida et al 55 and Jenkins et al 56 The panel recommends HER2 IHC testing (with reflex to HER2 fluorescence in situ hybridization for equivocal IHC) for possible treatment of advanced-stage or recurrent serous endometrial carcinoma or carcinosarcoma. HER2 IHC testing should also be considered in TP53-mutated/p53 abnormal endometrial carcinoma regardless of histotype.…”
Section: Pathologysupporting
confidence: 78%
“…HER2 overexpression in UCS has also been studied recently, and ORRs were around 10–20% in UCS [ 6 , 49 , 50 ]. Although there is no clinical trial data using HER2-targeting agents in treating UCS, a phase II trial revealed that a trastuzumab add-on to carboplatin and paclitaxel prolonged PFS more than chemotherapy alone in stage III/IV HER2/neu over-expressed serous endometrial cancer [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no clinical trial data using HER2-targeting agents in treating UCS, a phase II trial revealed that a trastuzumab add-on to carboplatin and paclitaxel prolonged PFS more than chemotherapy alone in stage III/IV HER2/neu over-expressed serous endometrial cancer [ 51 ]. Since these HER2-overexpressed UCS usually had a serous histology [ 49 , 50 ], HER2-targeted therapy would be a reasonable option in UCS with a serous component. We also had some patients with a check of HER2 IHC stain ( n = 10/98).…”
Section: Discussionmentioning
confidence: 99%
“…HER2 overexpression is also seen in USCs. Several studies have shown that 6% of USCs express HER2 IHC3 + and 15% of USCs express FISH + ( Jenkins et al, 2022 ). A preclinical study has revealed that T-DM1 seems to have a therapeutic effect on primary HER2-overexpressing USCs.…”
Section: T-dm1 Plays a Promising Therapeutic Role On Other Types Of C...mentioning
confidence: 99%